Association between the depression and cardiovascular risk in arthritis patients: a prospective cohort study from the CHARLS database - Tian, Xiaoyuan; Yang, Xianglin; Cao, Ying; Qu, Zhenan; Zhang, Bocheng (Frontiers in Immunology, 2025)
ObjectiveTo investigate the association between depression and cardiovascular disease (CVD) risk in arthritis patients and evaluate the modifying role of systemic inflammation.MethodsUsing data from the China Health and Retirement Longitudinal Study (CHARLS), we conducted a prospective cohort analysis of 2,571 arthritis patients without baseline CVD. Depression severity was assessed using the 10-item CES-D scale, with scores ≥12 defining depression. Multivariable logistic regression and restricted cubic spline (RCS) models analyzed dose-response relationships. We utilized C-reactive protein (CRP) to assess whether inflammatory status in arthritis patients modify this relationship. Sensitivity analyses included multiple imputation and complete-case approaches.ResultsEach 1-point increase in CES-D score elevated CVD risk by 2.8% (OR=1.028, 95% CI 1.012–1.044). High inflammation amplified CVD risk exclusively in depressed patients (OR=1.52 vs. OR=1.32 in low-inflammation depressed group), with no significant association in non-depressed individuals. Diabetes mellitus synergistically intensified this relationship (OR=2.83 in diabetic vs. OR=1.21 in non-diabetic depressed patients, P = 0.03 for interaction). Results remained robust across sensitivity analyses.ConclusionDepression linearly increases CVD risk in arthritis patients, with systemic inflammation selectively potentiating this association in depressed individuals. The diabetes-depression-CVD interaction highlights shared pathophysiological pathways. These findings underscore the imperative for integrated clinical strategies targeting both psychological health and inflammatory pathways to reduce cardiovascular morbidity in arthritis populations.